Analytical modeling of the shear behavior of rock joints with two-order asperity dilation and degradation - L,i Y. (2021)
Stability evaluation of rock structures requires a reliable model to assess the shear behavior of rock joints. This study reports an analytical model to predict the complete shear process of rock joints, and particularly considers the nonlinear shear behavior with two-order asperity dilation and degradation. The nonlinear variation of shear stress is characterized by the stepwise process of asperity evolution, which is quantified based on the classic wear theory. The dilation angles of two-order asperities decrease as a function of plastic tangential work as well as degradation coefficients of waviness and unevenness. The realistic descriptions of asperity degradation together with the basic friction angle and asperity dilation improve the prediction of joint shear behavior. The analytical results derived from the proposed model agree with the experimental data obtained from the direct shear tests on both regularly and irregularly shaped joints. The comparison among the proposed and other well-known constitutive models shows that this model is well established but can be improved by considering the roles of produced debris and failed asperities in the shear process.